Perancangan Sistem Informasi Penjualan Boneka Pada Store Adede Menggunakan Metode Waterfall - Nurfajria, Dera; Tukino, Tukino; Hananto, Agustia; Hananto, April Lia (STMIK Banjarbaru, 2025)
Digitalization of sales systems is an important need to improve transaction efficiency and accuracy. This study aims to build a web-based doll sales system at Toko Adede Cikampek using the Waterfall method which includes needs analysis, design, implementation, testing, and maintenance. The system was developed using PHP and MySQL, and tested using the black box method and System Usability Scale (SUS). The test results showed that all features ran as expected, with a SUS score of 83.3 which is classified as